Active-passive integrated vibration control for control moment gyros and its application to satellites. (28th April 2017) - Zhang, Yao; Zang, Yue; Li, Mou; Wang, Youyi; Li, Wenbo
Abstract: The strategy of active-passive integrated vibration control on the truss enveloping control moment gyroscopes (CMGs) is presented and its characteristics of time domain and frequency domain are analyzed. Truss enveloping CMGs contains pyramid-type CMGs, which are enveloped by multiple struts. These struts can be employed to realize the active-passive integrated vibration control. In addition, the struts of the trusses can maintain the working space of CMGs. Firstly, the disturbance characteristics of CMGs are analyzed considering static and dynamic imbalances of the CMG's rotor; then, an active-passive integrated vibration isolation truss structure is developed based on its characteristics. This structure can restrain the CMG vibration as much as possible and reduce its influence on the photographic quality of optical payloads. Next, the dynamic model of the active-passive vibration isolation truss structure is established. The frequency domain analysis of this model shows that the active-passive integrated vibration control method can restrain the high-frequency vibration and also improve the characteristics of low-frequency vibration. Finally, the dynamic model for the whole satellite is built with this type of CMGs. The time domain simulations of satellite attitude control verify the attitude control improvements resulting from the CMGs vibration control strategy. Highlights: We designed an integrated vibration control method of Control Moment Gyroscope. Dynamic models of integrated control truss structures are built. Characteristics of integrated control method are analyzed. The attitude control improvements through new control method are showed.